Intraoperative allogeneic transfusion is associated with postoperative delirium in older patients after total knee and hip arthroplasty - OuYang, Chun-lei; Hao, Xin-yu; Yu, Yao; Lou, Jing-sheng; Cao, Jiang-bei; Yu, Ying-qun; Mi, Wei-dong (Frontiers in Surgery, 2023)
Objective: To determine whether the intraoperative transfusion of allogeneic or autologous blood is associated with an increased incidence of POD after TKHA. Methods: The medical records of 1,143 older (≥65 years old) patients who received an intraoperative blood transfusion while undergoing total knee or hip arthroplasty at the First Medical Center of Chinese PLA General Hospital from 2014 to 2019 were reviewed; of these patients, 822 (66.94%) received allogeneic blood, while 406 (33.06%) received autologous blood. The primary outcome was POD. The secondary outcomes were postoperative complications, including heart failure, deep vein thrombosis, myocardial infarction, stroke, and lung infection. A multivariate nominal logistic regression was used to identify any independent associations between intraoperative blood transfusions and POD.Results: Postoperative delirium occurred in 6.6% (49/742) of patients who had received an allogeneic blood transfusion and in 2.0% (8/401) of patients who had received an autologous blood transfusion. It is noteworthy that the multivariable logistic regression demonstrated a significant association between intraoperative allogeneic blood transfusion and POD (odds ratio [OR]: 3.418; 95% confidence interval [CI]: 1.583–7.369; p < 0.001). The rate of postoperative lung infection was 0.5% (2/401) in patients who had received an autologous blood transfusion and 3.4% (28/742) in patients who had received an allogeneic blood transfusion (p = 0.002). Allogeneic transfusion was the strongest predictor for lung infection (OR: 6.731; 95% CI: 1.585–28.577; p = 0.010).Conclusions: In the patients who had received THA or TKA, intraoperative allogeneic blood transfusions were associated with an increased risk of POD.